A chiral luminescent liquid crystal with a tolane unit. Issue 6 (2nd May 2016) - Cheng, Zhihui; Zang, Ying; Li, Yi; Li, Baozong; Hu, Chuanjiang; Li, Hongkun; Yang, Yonggang
ABSTRACT: We have synthesised a chiral liquid crystal with a tolane unit that exhibits intense fluorescence in both solution and the solid states. The liquid crystal can form the enantiotropic twist-grain boundary A (TGBA *) and Blue II phases, and the helical pitch of the TGBA * phase decreases with an increasing temperature. Graphical Abstract: